Effect of intrauterine injection of human chorionic gonadotropin before frozen–thawed embryo transfer on pregnancy outcomes in women with endometriosis. Issue 7 (July 2019) - Xu, Zhihui; Chen, Wenming; Chen, Chune; Xiao, Yikang; Chen, Xia
Objective: To investigate the effect of human chorionic gonadotropin (hCG) intrauterine injection before frozen–thawed embryo transfer (FET) in women with endometriosis. Methods: This retrospective cohort study included 45 women with endometriosis who underwent hCG intrauterine injection before FET; each woman was matched with three patients with endometriosis who did not receive hCG intrauterine injection (controls). Data on pregnancy and prenatal outcomes were extracted from medical records and compared. Results: Patients in the hCG intrauterine injection group had significantly higher rates of pregnancy and clinical pregnancy (64.4% and 57.8%, respectively) than controls (47.4% and 39.3%, respectively). Neonatal birth weight for both singletons and twins was significantly higher in the hCG group (3486 ± 458 g and 2710 ± 437 g, respectively) than in the control group (3195 ± 401 g and 2419 ± 370 g, respectively). Conclusion: Pregnancy rate, clinical pregnancy rate, and birth weight were improved in women with endometriosis who underwent intrauterine hCG injection compared with those who did not receive hCG before FET.